4D Printing of Multi‐Responsive Membrane for Accelerated In Vivo Bone Healing Via Remote Regulation of Stem Cell Fate. (11th July 2021) - You, Dongqi; Chen, Guancong; Liu, Chao; Ye, Xin; Wang, Shaolong; Dong, Minyi; Sun, Mouyuan; He, Jianxiang; Yu, Xiaowen; Ye, Guanchen; Li, Qi; Wu, Junjie; et al.
Abstract: Dynamic regulation of substrate micro‐structures is an effective strategy to control stem cell fate in tissue engineering. Translating this into in vivo tissue repair in a clinical setting remains challenging, which requires precise temporal control of multi‐scale structural features. Using 4D printing technique, a multi‐responsive bilayer morphing membrane consisting of a shape memory polymer (SMP) layer and a hydrogel layer, is fabricated. The SMP layer is featured with responsive surface micro‐structures, which can switch the phase between proliferation and differentiation precisely, thus promoting the bone formation. The hydrogel layer endows the membrane with the ability to digitally regulate its 3D geometry, matching the specific macroscopic bone shape in clinical scenario. The authors' in vivo experiments show that the 4D shape‐shifting membrane exhibits over 30% improvement in new bone formation in comparison to a reference membrane with static micro‐structure. More importantly, the 4D membrane can conformally wrap a bone defect model in a non‐invasive way and this strategy can be extended to repairs involving complex tissue defects. Abstract : Dynamic regulation of substrate micro‐structures is an effective strategy to control stem cell fates. Taking it into a bone defect model, through DLP technology, a multi‐responsive bilayer morphing membrane with a shape memory polymer inside and programmable hydrogel outside, called a 4D printed membrane, provides the mechanism for macroscopic fitting for geometrically complex bone shapes and accelerated bone repair.